Effects of chronic moderate alcohol consumption on right ventricle and pulmonary remodelling. Issue 6 (23rd March 2021) - Silva, Ana Filipa; Sousa‐Nunes, Fábio; Faria‐Costa, Gabriel; Rodrigues, Ilda; Guimarães, João Tiago; Leite‐Moreira, Adelino; Henriques‐Coelho, Tiago; Negrão, Rita; Moreira‐Gonçalves, Daniel
Abstract : New Findings: What is the central question of this study? Does the consumption of a moderate amount of alcohol differentially impact the heart ventricles and pulmonary vasculature. What is the main finding and its importance? Moderate alcohol consumption for a short period of time impaired pulmonary vascular cellular renewal through an apoptosis resistance pattern that ultimately affected the right ventricular function and structure. These findings support the need for a deeper understanding of effects of moderate alcohol consumption on the overall cardiovascular and pulmonary systems. Abstract: Over the past decades, observational studies have supported an association between moderate alcohol consumption and a lower risk of cardiovascular disease and mortality. However, recent and more robust meta‐analyses have raised concerns around the robustness of the evidence for the cardioprotective effects of alcohol. Also, studies of the functional, structural and molecular changes promoted by alcohol have focused primarily on the left ventricle, ignoring the fact that the right ventricle could adapt differently. The aim of this study was to evaluate the bi‐ventricular impact of daily moderate alcohol intake, during a 4‐week period, in a rodent model. Male Wistar rats were allowed to drink water (Control) or a 5.2% ethanol mixture (ETOH) for 4 weeks. At the end of the protocol bi‐ventricular haemodynamic recordings were performed and samples collected for further histological and molecular analysis. ETOH ingestion did not impact cardiac function. However, it caused right ventricle hypertrophy, paralleled by an activation of molecular pathways responsible for cell growth (ERK1/2, AKT), proteolysis (MURF‐1) and oxidative stress (NOX4, SOD2). Furthermore, ETOH animals also presented remodelling of the pulmonary vasculature with an increase in pulmonary arteries' medial thickness, which was characterized by increased expression of apoptosis‐related proteins expression (BCL‐XL, BAX and caspases). Moderate alcohol consumption for a short period of time impaired the lungs and the right ventricle early, before any change could be detected on the left ventricle. Right ventricular changes might be secondary to alcohol‐induced pulmonary vasculature remodelling. Abstract :